2020
DOI: 10.1002/cbf.3534
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐302b‐5p enhances the neuroprotective effect of IGF‐1 in methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine‐induced Parkinson's disease by regulating inducible nitric‐oxide synthase

Abstract: Parkinson's disease (PD) is a neurodegenerative disease which results in damage in neuronal cells. Insulin-like growth factor (IGF)-1 was previously reported to play a role of neuroprotection in some diseases. Nitric oxide (NO) can also regulate neuronal cells. However, the mechanisms underlying IGF-1 and NO in PD still need to be elucidated. In present study, we explored the interaction between IGF-1 and inducible Nitric-Oxide Synthase (iNOS) in PD progression. We firstly constructed PD models by methyl-4-phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…miRNA can regulate arginine metabolism by regulating the expression of key molecules in arginine metabolism pathway, such as ASS ( Bates et al, 2010 ; Tu et al, 2020 ), ARG1 ( Bates et al, 2010 ; Yoo et al, 2019 ), ARG2 ( Dunand-Sauthier et al, 2014 ; Jin et al, 2014 ; Kim et al, 2017 ; Wang Y. et al, 2017 ), CAT-1 ( Chang et al, 2004 ; Li Y. et al, 2018 ), ODC ( Jagannathan et al, 2015 ) and NOS ( Perske et al, 2010 ; Yan et al, 2011 ; Guo et al, 2012 ; Sun et al, 2012 ; Zhu et al, 2013 ; Li et al, 2014 , 2017 , Li H.T. et al, 2018 ; Fu et al, 2015 ; Jiang et al, 2015 ; Zhang et al, 2015 , 2020 ; Rasheed et al, 2016 ; Reilly et al, 2016 ; Muxel et al, 2017 , 2018 ; Wang C. et al, 2017 , Wang et al, 2019 ; Cui et al, 2020 ; Lin et al, 2020 ; Scalavino et al, 2020 ; Table 1 ). It has been found that multiple miRNAs could target the same enzyme or transporter protein, and the same molecule could also be regulated by multiple miRNAs.…”
Section: Mirnas and Long Non-coding Rnas In Arginine Metabolism And Crcmentioning
confidence: 99%
“…miRNA can regulate arginine metabolism by regulating the expression of key molecules in arginine metabolism pathway, such as ASS ( Bates et al, 2010 ; Tu et al, 2020 ), ARG1 ( Bates et al, 2010 ; Yoo et al, 2019 ), ARG2 ( Dunand-Sauthier et al, 2014 ; Jin et al, 2014 ; Kim et al, 2017 ; Wang Y. et al, 2017 ), CAT-1 ( Chang et al, 2004 ; Li Y. et al, 2018 ), ODC ( Jagannathan et al, 2015 ) and NOS ( Perske et al, 2010 ; Yan et al, 2011 ; Guo et al, 2012 ; Sun et al, 2012 ; Zhu et al, 2013 ; Li et al, 2014 , 2017 , Li H.T. et al, 2018 ; Fu et al, 2015 ; Jiang et al, 2015 ; Zhang et al, 2015 , 2020 ; Rasheed et al, 2016 ; Reilly et al, 2016 ; Muxel et al, 2017 , 2018 ; Wang C. et al, 2017 , Wang et al, 2019 ; Cui et al, 2020 ; Lin et al, 2020 ; Scalavino et al, 2020 ; Table 1 ). It has been found that multiple miRNAs could target the same enzyme or transporter protein, and the same molecule could also be regulated by multiple miRNAs.…”
Section: Mirnas and Long Non-coding Rnas In Arginine Metabolism And Crcmentioning
confidence: 99%
“…MPTP remarkably induces DAergic neuron loss by activating the iNOS/NO/pathway in microglia cells, which results in the reduction of DA levels . Results showed that MPTP remarkably increased the NO level and decreased the DA level in the SNpc and striatum (STR) compared with the control group.…”
Section: Results and Discussionmentioning
confidence: 98%
“…MPTP remarkably induces DAergic neuron loss by activating the iNOS/NO/pathway in microglia cells, which results in the reduction of DA levels. 28 Results showed that MPTP remarkably increased the NO level and decreased the DA level in the SNpc and striatum (STR) compared with the control group. However, pre-treatment with 18 remarkably decreased the NO level and increased the DA level in the SNpc and STR compared with the MPTP group (Figure 8A,B).…”
Section: ■ Introductionmentioning
confidence: 97%
“…The results of the present study suggested that inhibition of IGF-1 by exogenous methods could inhibit the growth of prolactinoma and reduce the secretion of PRL and GH. In vivo, IGF-1 is also targeted by miRNAs (31,32). In polycystic ovary syndrome, IGF-1 is targeted by miR-323-3p and miR-323-3p/IGF-1 is involved in the regulation of steroid secretion and human cumulus cell function (33).…”
Section: Discussionmentioning
confidence: 99%